Metastatic anaplastic large cell lymphoma of the oral cavity - Parviz Deyhimi; Forouz Keshani; Faezeh Azmoudeh; Zahra Hashemzadeh (Wolters Kluwer Medknow Publications, 2012)
Lymphoma is a malignant neoplasm of lymphoid tissue which is divided into 2 groups: Hodgkin and non-Hodgkin. About 85% of non-Hodgkin lymphomas are B-cell lymphomas, and T-cell lymphomas are unusual. Anaplastic large cell lymphoma (ALCL) is a kind of non-Hodgkin lymphoma with T or NK cell origin that is rarely seen in the oral cavity and only 10 cases have been reported up to now. Here we present a case of ALCL metastasized to the oral cavity in a 32- year- old man with pervious history of ALCL which caused an ulceration in the posterior area of the hard palate. Radiography showed irregular resorption of alveolar bone. Histopathologic examination of the incisional biopsy revealed neoplastic proliferation of large and bizarre cells with hyperchromatic nuclei and numerous giant cells and atypical mitoses. Immunohistochemistry markers (CK, LCA, CD3, CD30, CD20) confirmed the diagnosis of ALCL.